Don’t be a victim: recognising financial scams in Malaysia - Sahrim, Azila; Zainal Abidin, Nurain Farahana; Ali, Asiah; Kamarulzaman, Masrul Hayati; Idris, Asma’ Rashidah; Zoolkefli, Zuliana; Zulkifli, Ahmad Farouk (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2025)
The rapid growth of digital technology and online financial services has made money management more convenient but has also increased the risk of financial scams in Malaysia. Bank Negara Malaysia has warned the public through its Financial Fraud Alerts campaign about various scams that threaten individuals and the financial system. Common methods include phishing and smishing, where scammers use fake emails, websites, or messages that imitate legitimate financial institutions to trick victims into revealing sensitive information such as banking credentials, credit card details, or OTPs.